Analyses of temporal dynamics of brown rot development on fruit in organic apple production - Holb, I. J. (International Journal of Horticultural Science, 2003)
In a two-year study, yield loss and temporal dynamics of brown rot development caused by Monilinia fructigena (Aderh. & Ruhl.) Honey were quantified and analysed in two organic apple orchards (Debrecen—Pallag and Debrecen—Józsa). The first infected fruits were observed at the beginning of August in both years and both locations, except for one occasion when the first infected fruit was found at the end of July. Temporal disease development was continuous up to harvest time in both years and locations. In the two years, pre-harvest yield loss on the trees amounted between 8.9% and 9.3% at Debrecen-Pallag and between 9.7% and 10.8% at Debrecen—Jozsa by fruit harvest. Incidence of infected fruits on the orchard floor ranged from 32.4% to 43.2% and from 53.3% to 61.9%, at Debrecen—Pallag and Debrecen—Józsa, respectively, by fruit harvest. Analyses of temporal disease progress showed that the best-fitted mathematical function was the power function in both orchards and years. Both parameters of the power function clearly demonstrated that incidence of brown rot on fruit increased faster on the orchard floor than on the tree. Moreover, the disease increase was faster at Debrecen—Józsa in most cases than at Debrecen—Pallag. Our results indicated that the strategy of disease management, the ripeness of the fruit and the presence of a wounding agent played an important role in the yield loss and in the temporal development of fruit disease incidence caused by M. fructigena in organic apple orchards. Biological and practical implications of the results are discussed.